Analysis of Character Education Programs for Developing Students’ Morals in Elementary Schools - Nopita Sari; Muhammad Dhori; Yora Penisa; Melia Anggriani; Riopaldo (Program Studi PGSD Universitas Madako Tolitoli, 2025)
Character education within the educational system shapes moral and ethical values, contributing to the development of a generation that possesses honesty, responsibility, courage, faith, piety, and a high sense of dignity. This study aims to examine the influence of character education on the moral formation of students at SDN 13 Pagar Gunung, focusing on aspects of discipline, responsibility, honesty and empathy. Through a qualitative approach with a case study design, data was collected through in-depth interviews with teachers and observations of students' behaviour. The results show that the implementation of character education at SDN 13 Pagar Gunung has a positive impact on students' moral development. The character education programme, which involves activities such as congregational prayer, collective prayer, extracurricular activities and collaboration with parents, has improved students' discipline, honesty, responsibility and empathy. The research also emphasises the importance of collaboration between school, home and community in supporting students' character building. The findings are expected to contribute to the development of a more practical character education model, in accordance with Indonesia's socio-cultural conditions, as well as supporting a holistic education policy, creating students who are not only smart but also moral.